Financial Statement Detection Using Fraud Diamond - Menik Indrati; Nadya Claraswati (Journal Research of Social Science, Economics, and Management, 2021)
This study aims to detect fraudulent financial statements using the theory fraud diamond. Financial statement fraud is measured using the Modified Jones Model. Disclosure of accrued income from credit sales and accrued receivables of the company is the reason for using the Modified Jones Model. In this study, the authors add the use of the receivables ratio as a proxy variable from the nature of the industry so that the most suitable research model used in detecting financial statement fraud is using the Modified Jones Model. The population in this study are all property and sector companies real estate listed on the Indonesia Stock Exchange for the 2015-2019 period. The sample in this study was 20 companies (100 company data with an observation period of 5 years) in the property and sector real estate listed on the Indonesia Stock Exchange from 2015 to 2019. Using multiple linear regression statistical methods and hypothesis testing using SPSS version 26. This study indicates that financial stability, target, and auditor change do not affect financial statement fraud. Meanwhile, external pressure, the nature of the industry, and total accruals affect fraudulent financial statements.